A Subtitling Analysis Of Swearing Words Found In Transformer 3: Dark Of The Moon - Prihartanti, Yuni (2012)
This research paper deals with swearing expression found in Transformer 3: Dark of the Moon and Its Subtitle. This research is conducted to describe and identify the linguistics form and the second is conducted to describe and identify the linguistics meaning of swearing words. The third is conducted to describe and identify and the last is conducted to describe and identify the equivalence of swearing words and the subtitle variation of swearing words. The type of this research is descriptive qualitative. The data source of this research is taken from a movie entitled Transformer 3: Dark of the Moon and Its Subtitle. The data are all utterances which deal with swearing expression taken from them. The writer takes 110 data of swearing words found in this movie. The results of the study show: 1) The linguistics forms are: word 37 %; phrase 18 %; clause 2 %; and sentence 43 %. 2) The linguistics meaning are: insult 28, 2%; curse 13, 64%; insist 23, 64%; vow4, 54%; annoyance4, 54%; disappointment 14, 54% and blaspheme10, 90%. 3) The equivalence is: equivalence at word level 42, 72%; equivalence above word level 22, 72%; grammatical equivalence 10%; textual equivalence 6, 36% and pragmatic equivalence 18, 2%. 4) The subtitle variation of swear expressions are: level shifts 24, 54%. and category shifts is divided into four types, such as: structure shifts 19, 19%; class shifts 25, 45%; unit shifts 20% and intra-system shifts 7, 27% and the last is non variation found 3, 64%.